2008
DOI: 10.1021/jo800228e
|View full text |Cite
|
Sign up to set email alerts
|

CeCl3·7H2O: An Effective Additive in Ru-Catalyzed Enantioselective Hydrogenation of Aromatic α-Ketoesters

Abstract: In the presence of catalytic amounts of CeCl 3.7H 2O, [RuCl(benzene)(S)-SunPhos]Cl is a highly effective catalyst for the asymmetric hydrogenation of aromatic alpha-ketoesters. A variety of ethyl alpha-hydroxy-alpha-arylacetates have been prepared in up to 98.3% ee with a TON up to 10,000. Challenging aromatic alpha-ketoesters with ortho substituents are also hydrogenated with high enantioselectivities. The addition of CeCl 3.7H 2O not only improves the enantioselectivity but also enhances the stability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 87 publications
2
67
0
Order By: Relevance
“…1a) as the catalyst. Sparked by Zhang group's work [17], we introduced cerium It is well known that asymmetric transfer hydrogenation (ATH) is an alternative to asymmetric hydrogenation (AH) because this method does not need either pressure vessels or hydrogen gas and can be carried out in ordinary laboratories, however, to the best of our knowledge, there are no reports about the preparation of methyl (R)-o-chloromandelate via asymmetric transfer hydrogenation (ATH). For exploring the possibility of ATH as a key strategy in asymmetric synthesis of (S)-Clopidogrel, we first chose Ts-DPEN (5a), a widely used chiral ligand in the catalytic asymmetric transfer hydrogenation of ketones, for the Ru-catalyzed ATH of methyl o-chlorobenzoylformate (compound 3) (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) as the catalyst. Sparked by Zhang group's work [17], we introduced cerium It is well known that asymmetric transfer hydrogenation (ATH) is an alternative to asymmetric hydrogenation (AH) because this method does not need either pressure vessels or hydrogen gas and can be carried out in ordinary laboratories, however, to the best of our knowledge, there are no reports about the preparation of methyl (R)-o-chloromandelate via asymmetric transfer hydrogenation (ATH). For exploring the possibility of ATH as a key strategy in asymmetric synthesis of (S)-Clopidogrel, we first chose Ts-DPEN (5a), a widely used chiral ligand in the catalytic asymmetric transfer hydrogenation of ketones, for the Ru-catalyzed ATH of methyl o-chlorobenzoylformate (compound 3) (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Genet et al developed the Ru-catalyzed asymmetric hydrogenation of a-keto ester to afford (R)-o-chloromandelate with 50% ee [15]. Zhang et al reported the asymmetric hydrogenation of the corresponding ethyl ester with enantioselectivity of up to 78.2% ee [16,17]. In our previous study, we reported a total synthesis of (R)-Salmeterol, a selective long-acting b 2 -adrenoreceptor agonist, via asymmetric transfer hydrogenation for preparing the chiral secondary alcohol which is the key intermediate in the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral data were in agreement with reported literature values. 47 1 H NMR (500 MHz, CDCl 3 ) δ 8.02 (dd, J = 1.1, 8.0 Hz, 2H), 7.67 (td, J =1.1, 7.8 Hz, 1H), 7.53 (dd, J = 7.8, 7.8 Hz, 2H), 4.47 (q, J = 7.2, 2H), 1.44 (t, J = 7.2 Hz, 3H).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction rate could be accelerated by adding 1.06 equiv t BuOK, and the full conversion was obtained within 2 h (Table 1, entry 4). Solvent screening showed that n-butanol 75 gave the best enantioselectivity (Table 1, entries 5−8). By comparison of various chiral SpiroPAP ligands, it was found that the introduction of an alkyl group at the 6-position of the pyridine ring of the ligand reduced the enantioselectivity (compare entry 12 with entry 9), however, the presence of an alkyl group at either the 3-or 4-position of the pyridine ring could increase the enantioselectivity (compare entries 8 and 10 with entry 9).…”
mentioning
confidence: 99%